Generation of picosecond UV pulses by an Nd3+:YAG laser for amplification in an ArF amplifier. (31st March 2015) - Sadovskiy, S P; Chizhov, P A; Bukin, V V; Brendel', V M; Dolmatov, T V; Polivanov, Yu N; Vorob'ev, N S; Smirnov, A V; Garnov, S V; Vartapetov, S K
Abstract The scheme generating UV pulses with a duration 15 ps and output energy up to 11.5 mJ is implemented in the system consisting of a picosecond Nd3+:YAG laser with multistage nonlinearoptical conversion of fundamental frequency radiation into radiation with a wavelength 193 nm followed by an excimer ArF amplifier. The temporal characteristics and the contrast of the amplified pulses are measured.